Unmanned Aerial Vehicle Based Wireless Sensor Network for Marine-Coastal Environment Monitoring - Trasviña Moreno, Carlos Andrés; Blasco Marín, Rubén; Marco Marco, Alvaro; Casas Nebra, Roberto (Jornada de Jóvenes Investigadores del I3A, 2017)
A UAV-bouy hybried Wireless Sensor Network, with LoRa communications, is presented for the monitorization of marine-coastal environments. This implementation offers a low-power, long-range and cost-effective solution to current marine monitoring applications, as well as a safer method to observing natural protected areas and reservoirs.